2020
DOI: 10.3389/fonc.2020.01432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Changes in Preoperative and Postoperative Serum CA19-9 Levels in Gastric Cancer

Abstract: Objective: The prognostic significance of serum CA19-9 levels in gastric cancer patients remains a matter debate. The aim of this study was to determine the prognostic value of changes in preoperative and postoperative serum CA19-9 levels in patients with gastric cancer. Methods: A total of 1,046 gastric cancer patients who underwent curative gastrectomy in West China Hospital of Sichuan University from January 2011 to December 2016 were analyzed retrospectively. Patients were categorized by minimum P-value us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The change in serum CA199 levels before and after surgery has been confirmed to be an independent prognostic factor for gastric cancer patients. 20 However, when we conducted data statistics, we found that most of the patients’ tumor markers were within the normal range and not higher than the normal value. The size of tumor tissue, blood supply, differentiation of tumor cells, and tumor stage all affect the concentration of tumor markers to varying degrees.…”
Section: Discussionmentioning
confidence: 83%
“…The change in serum CA199 levels before and after surgery has been confirmed to be an independent prognostic factor for gastric cancer patients. 20 However, when we conducted data statistics, we found that most of the patients’ tumor markers were within the normal range and not higher than the normal value. The size of tumor tissue, blood supply, differentiation of tumor cells, and tumor stage all affect the concentration of tumor markers to varying degrees.…”
Section: Discussionmentioning
confidence: 83%
“…However, patients with similar pathological features often presented diverse survival outcomes. Although the prognostic significance of certain inflammatory markers ( 2 , 3 ) and tumor markers ( 4 , 5 ) in GC have already been certified, we need to identify more prognostic markers that are inexpensive to test and easily available before treatment for enabling precision prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Serum tumor markers, indirectly indicating tumor burden, are commonly used for malignant tumor diagnosis, e cacy evaluation, and prognosis [22][23][24]. Lang D et al demonstrated that the early change of serum tumor markers is predictive of progression-free and overall survival in patients with NSCLC treated by PD-1 targeted therapy [25].…”
Section: Diagnostic Performance Of Signaturesmentioning
confidence: 99%